2020
DOI: 10.1055/s-0040-1721515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Excess Perinatal Mortality and Morbidity in Israel

Abstract: Objective The 2020 COVID-19 pandemic has been associated with excess mortality and morbidity in adults and teenagers over 14 years of age, but there is still limited evidence on the direct and indirect impact of the pandemic on pregnancy. We aimed to evaluate the effect of the first wave of the COVID-19 pandemic on obstetrical emergency attendance in a low-risk population and the corresponding perinatal outcomes. Study Design This is a single center retrospective cohort study of all singleton birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 21 publications
7
74
2
1
Order By: Relevance
“…Another study conducted at a London hospital [6] did not find this decline but showed an increase in stillbirths following the COVID-19 pandemic. This was also found in a single-center retrospective cohort study [7]. However, a most robust study including regional and national data in England found no link between stillbirths and lockdown [8].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Another study conducted at a London hospital [6] did not find this decline but showed an increase in stillbirths following the COVID-19 pandemic. This was also found in a single-center retrospective cohort study [7]. However, a most robust study including regional and national data in England found no link between stillbirths and lockdown [8].…”
Section: Discussionsupporting
confidence: 57%
“…Whether the behavior of prematurity rates is consistent with and in a similar proportion to what is seen in other parts of Europe is not known. In fact, two single-center studies showed a higher rate of stillbirths [6,7], although this was not subsequently corroborated in a more robust national study in England [8].…”
Section: Introductionmentioning
confidence: 91%
“…This was also found in a single center retrospective cohort study. [7] However, a most robust study including regional and national data in England found no link between stillbirths and lockdown. [8] Furthermore, the approach to prematurity rate research was not the same in all the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Whether the behavior of prematurity rates is consistent with and in a similar proportion to what is seen in other parts of Europe is not known. In fact, two a single center studies showed a higher rate of stillbirths, [6,7] although this was not subsequently corroborated in a more robust national study in England. [8] Our aim was to explore, in a population-based prevalence proportion study, the potential link between national lockdown measures and changes in preterm births and stillbirths.…”
Section: Introductionmentioning
confidence: 92%
“…A recent study by Mor et al (2021) assessed the impact of the pandemic on emergency obstetric care and on perinatal outcomes in a low-risk population in Israel. Authors identified that during the first wave of COVID-19 in Israel (from February to April 2020), emergency child delivery hospitalizations were lower on average when compared to the same period in the preceding years (2017-2019) 30 . Moreover, they found a significantly higher rate (p=0.037) of stillbirths during the study period.…”
Section: Discussionmentioning
confidence: 99%